2022
DOI: 10.3389/fimmu.2022.982155
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of 3 doses of BNT162b2 and CoronaVac in children and adults with inborn errors of immunity

Abstract: Our study (NCT04800133) aimed to determine the safety and immunogenicity in patients with IEIs receiving a 3-dose primary series of mRNA vaccine BNT162b2 (age 12+) or inactivated whole-virion vaccine CoronaVac (age 3+) in Hong Kong, including Omicron BA.1 neutralization, in a nonrandomized manner. Intradermal vaccination was also studied. Thirty-nine patients were vaccinated, including 16 with homologous intramuscular 0.3ml BNT162b2 and 17 with homologous intramuscular 0.5ml CoronaVac. Two patients received 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Several studies in general population have raised the importance of booster for a greater protection against SARS-CoV-2 infection and leads to reduce disease severity. Among IEI patients the third doses of BNT162b2 reduces the seroconversion failure from 45% to 26% ( 37 ), similar results from Shields et al, reducing the seroconversion failure from 39 to 34% in IEI patients ( 38 ). However, there are still some IEI patients that failed to produce antibody response or a T cell response.…”
Section: Discussionsupporting
confidence: 66%
“…Several studies in general population have raised the importance of booster for a greater protection against SARS-CoV-2 infection and leads to reduce disease severity. Among IEI patients the third doses of BNT162b2 reduces the seroconversion failure from 45% to 26% ( 37 ), similar results from Shields et al, reducing the seroconversion failure from 39 to 34% in IEI patients ( 38 ). However, there are still some IEI patients that failed to produce antibody response or a T cell response.…”
Section: Discussionsupporting
confidence: 66%
“…Such studies performed particularly in children and adolescents to prevent the spread of SARS‐CoV‐2 or development of post‐COVID‐19 condition are required 17,19,80 . There are minimal data on optimal immunization for those with immunocompromized conditions and comorbidities, which are absolutely necessary for protecting these vulnerable, high‐risk patients 81–84 . As primary vaccination rates have peaked with satisfactory coverage in most geographical regions by this time, newer generations of polyvalent vaccines must be thoroughly investigated in the future, especially in unvaccinated infants who have not been exposed to the virus on which there is currently minimal research 1,49–52,85 .…”
Section: Discussionmentioning
confidence: 99%
“…17,19,80 There are minimal data on optimal immunization for those with immunocompromized conditions and comorbidities, which are absolutely necessary for protecting these vulnerable, high-risk patients. [81][82][83][84] As primary vaccination rates have peaked with satisfactory coverage in most geographical regions by this time, newer generations of polyvalent vaccines must be thoroughly investigated in the future, especially in unvaccinated infants who have not been exposed to the virus on which there is currently minimal research. 1,[49][50][51][52]85 This will be essential to inform policymakers on their decision to incorporate COVID-19 vaccines in national immunization programs.…”
Section: Discussionmentioning
confidence: 99%
“…When the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic broke out in late 2019 [ 8 ], initial reports indicated increased disease-related morbidity and mortality in immunocompromised patients [ 9 , 10 , 11 , 12 , 13 ], including those with PAD [ 14 , 15 , 16 ]. After vaccines became available, several studies have investigated both the reactogenicity and immunogenicity of SARS-CoV-2 vaccines in PAD patients, and most studies concluded that the immune response in PAD patients was inferior to that in healthy vaccine recipients [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies with immunocompetent individuals have examined the correlates of SARS-CoV-2-specific humoral response and found changes in levels of M-CSF, IL-1α, IFN-γ, IL-1β, IL-10, IL-12p70, IL-6, IL-17A, IL-15, and IFN signaling-related cytokines (CXCL10, MCP-1, MCP-2, and MCP-3) to be correlated with SARS-CoV-2-specific antibody response in healthy volunteers [ 45 , 62 , 63 , 64 , 65 ]. Regarding PAD patients, several studies have examined the T cell response role in protection against SARS-CoV-2, showing IL-2 and/or IFN-γ secretion in response to pooled SARS-CoV-2 antigens [ 18 , 24 , 25 , 26 , 27 , 28 ]. Nonetheless, the understanding of the wider range of cytokines produced following SARS-CoV-2 antigen stimulation in individuals with predominantly antibody deficiencies is currently limited.…”
Section: Introductionmentioning
confidence: 99%